Quisqualate and L-glutamate inhibit retinal horizontal-cell responses to kainate. - Ishida, A T (1985)
Currents elicited by L-glutamate and the related agonists quisqualate and kainate were analyzed under voltage clamp in isolated goldfish horizontal cells, using the whole-cell recording configuration of the patch-clamp method [Hamill, O.P., Marty, A., Neher, E., Sakmann, B. & Sigworth, F. J. (1981) Pflügers Arch. 391, 85-100]. These currents resulted from an increase in cationic conductance and were indistinguishable from one another in terms of reversal potential (approximately equal to 0 mV) and apparent elementary conductance (2-3 pS). The power-density spectra of the noise increases produced by each agonist were fit by the sum of two Lorentzian curves having similar cutoff frequencies (tau 1 approximately equal to 5 msec, tau 2 approximately equal to 1 msec), but the relative power of these components were different for quisqualate and glutamate than for kainate. Moreover, the responses to high doses of either quisqualate or glutamate rapidly faded, whereas the responses to kainate did not. Finally, quisqualate and glutamate produced an inhibition of responses to kainate which appeared to be uncompetitive. Kainate, quisqualate, and in our preparation, glutamate appear to activate channels different than those activated by N-methyl-D-aspartate in other preparations. At least some of the effects of quisqualate and glutamate appear to be mediated by receptors bound by kainate.